[Maren Elisabeth Bang]: Huusholdnings-bog (1831) - Davidson, Alan E (Petits Propos Culinaires, 1993)
[Maren Elisabeth Bang]: Huusholdnings-bog (1831): Oslo, Bjørn Ringstrøms Antikvariat (Ullevålsv. I), 1993: 190 pp, introduction by Henry Notaker (with two-page summary in English), numbered copies, price not shown.